2013
DOI: 10.1007/s00018-013-1260-1
|View full text |Cite
|
Sign up to set email alerts
|

Properties and mechanisms of action of naturally occurring antifungal peptides

Abstract: Antimicrobial peptides are a vital component of the innate immune system of all eukaryotic organisms and many of these peptides have potent antifungal activity. They have potential application in the control of fungal pathogens that are a serious threat to both human health and food security. Development of antifungal peptides as therapeutics requires an understanding of their mechanism of action on fungal cells. To date, most research on antimicrobial peptides has focused on their activity against bacteria. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
170
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 238 publications
(176 citation statements)
references
References 260 publications
4
170
0
2
Order By: Relevance
“…This allows entry of the peptide into the cells, where it may have secondary targets such as DNA. It has been reported that antifungal peptides of animal as well as plant origin, such as the cysteine-rich family of AMPs, have intracellular targets and usually enter inside a cell either through receptor-mediated uptake or membrane permeabilization (5). In addition, proline-rich antifungal peptides have also been reported to translocate across the fungal membrane and interact with intracellular targets (51).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This allows entry of the peptide into the cells, where it may have secondary targets such as DNA. It has been reported that antifungal peptides of animal as well as plant origin, such as the cysteine-rich family of AMPs, have intracellular targets and usually enter inside a cell either through receptor-mediated uptake or membrane permeabilization (5). In addition, proline-rich antifungal peptides have also been reported to translocate across the fungal membrane and interact with intracellular targets (51).…”
Section: Resultsmentioning
confidence: 99%
“…Cryptococcus neoformans is a major opportunistic fungal pathogen, linked to cryptococcosis, which may cause infection in cutaneous, pulmonary regions or even in the brain meninges (4,5). Cryptococcal meningitis is a fatal disease especially seen in HIV patients, affecting >1,000,000 people annually and leading to a death toll of~70,000 worldwide (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…nnate immunity peptides have evolved in plants to protect against the damaging effects of microbial pathogens, particularly fungi (1). Fungi cause both persistent annual crop losses and devastating epidemics (2) that are a serious threat to global food security (3).…”
mentioning
confidence: 99%